The invisible educators: exploring the development of Teacher Educators in the Further Education system - Thurston, Diane (Teaching in Lifelong Learning: A Journal to Inform and Improve Practice, 2010)
This article outlines the scope of proposed case study research to be conducted from May 2010 and intended to explore factors which support the development of Teacher Educators (TEs) in post compulsory settings – a significantly under researched professional group. The article reviews the research literature in this area, identifying significant omissions, and presents an initial overview of the case to be explored. The article identifies models of Teacher Educator development, originating from English for Speakers of Other Languages (ESOL) and English as a Foreign Language (EFL) teacher education which will inform this research, as well as the role of Teacher Educator as researcher.